2012
DOI: 10.1007/s10703-012-0144-6
|View full text |Cite
|
Sign up to set email alerts
|

Constructive Boolean circuits and the exactness of timed ternary simulation

Abstract: We classify gate level circuits with cycles based on their stabilization behavior. We define a formal class of combinational circuits, the constructive circuits, for which signals settle to a unique value in bounded time, for any input, under a simple conservative delay model, called the up-bounded non-inertial (UN) delay. Since circuits with combinational cycles can exhibit asynchronous behavior, such as non-determinism or metastability, it is crucial to ground their analysis in a formal delay model, which pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 41 publications
(107 reference statements)
0
34
0
Order By: Relevance
“…The ideal is a situation like in [64] where it is shown that Berry's must-cannot analysis [12] when applied to circuits is (sound and) complete for scheduling under non-inertial delays. In another direction, it will be interesting to search for suitable, more expressive, extensions of the domain I (D, P) in which the fixed-point analysis of pSCL is complete for SC-constructiveness as defined in [86].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ideal is a situation like in [64] where it is shown that Berry's must-cannot analysis [12] when applied to circuits is (sound and) complete for scheduling under non-inertial delays. In another direction, it will be interesting to search for suitable, more expressive, extensions of the domain I (D, P) in which the fixed-point analysis of pSCL is complete for SC-constructiveness as defined in [86].…”
Section: Discussionmentioning
confidence: 99%
“…2 The only available result on the lower-level operational soundness of the fixed-point construction is indirect, has never formally been proven and applies to the hardware translation given in [12]. At the hardware level it is known that constructiveness implies delay-insensitivity under non-inertial delays [58,64,76]. While this highlights the universal nature of the constructive semantics, it does not provide insights into the nature of constructiveness for software implementations of SMoCC languages.…”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Shiple et al [1996] have grounded this parallel semantics in the physical models of Brzozowski and Seger [1995]. The connection with constructive logic continues to be explored by Mendler et al [2012], and Riedel and Bruck [2003] show that cycles can yield significant space reductions in practice.…”
Section: Circuit Semanticsmentioning
confidence: 99%